CO2 levels and SARS-CoV-2 transmission in public schools: A retrospective cohort study in Montreal (Canada) - Olivier Séguin; Dorra Ghorbal; Gabrielle Denault; Karine Trudeau; Patrick Poulin; Catherine Dea; Stéphane Perron (Indoor Environments)
Scientific evidence suggests that SARS-CoV-2 is transmitted primarily through close contact with susceptible individuals and that the risk of transmission increases during prolonged exposure in confined, inadequately ventilated and densely occupied spaces. In response to concerns related to inadequate ventilation for students and staff, CO2 concentrations were measured in all of Montreal’s public elementary and high schools during winter of 2020–21. This study aims to evaluate the associations between ventilation system types, mid-class CO2 concentrations and SARS-CoV-2 transmission amongst Montreal's public school’s attendees during the 2020–2021 school year. Data on building ventilation types, CO2 measurements and school characteristics such as total enrollment and socioeconomic status (SES), were sourced from Ministry of Education’s administrative data for the 2020–2021 school year. During this pandemic period, the Montreal Public Health Department investigated COVID-19 cases among students and staff in public elementary and high schools, gradually developing a regional database of school cases and outbreaks from intervention files. Negative binomial regression models were employed to examine associations between mid-class CO2 concentrations and COVID-19 incidence rates for both total cases and those acquired within schools. Regression models were adjusted for school types, neighborhood COVID-19 incidence rates and school SES. The mid-class CO2 concentrations median was 1050 ppm in the 384 school buildings. CO2 concentrations were associated with ventilation systems, with schools using natural ventilation exhibiting higher concentrations compared to three other types of mechanical ventilation. No positive association was observed between the incidence rates of school-acquired cases and higher mid-class CO2 concentrations in both unadjusted and adjusted models.